Continuing professional development for english language teachers in digital era - Irwandi Irwandi; Albert Albert (Fakultas Ilmu Pendidikan UNP)
English language teacher strives to raise standards of language teaching in the new global setting knowledge. Perhaps understandably, any efforts to improve language education quality cannot succeed without the continuous support and cooperation of a professional teacher. This fact is widely recognized in international attention mostly in term of promoting the continuing professional of teachers. The term of continuing refers to the need for ongoing development of teachers’ knowledge, professional skill, and their effectiveness in the classroom. This is a reaction to the professional development which is not satisfied yet in leading to an increase in teacher knowledge, skills, and commitment. This paper explores the concept of continuing professional development, the limitation of current approaches to professional development, and the reinvigoration strategy of professional development for English language teacher.